Africa’s contribution to global sustainable and healthy diets: a scoping review - Oniang’o, Ruth; Maingi, Zadok; Jaika, Silvester; Konyole, Silvenus (Frontiers in Nutrition, 2025)
BackgroundA healthy diet is essential for human wellbeing and environmental sustainability. Africa possesses diverse traditional food systems that are nutritionally rich and environmentally sustainable. However, modern dietary transitions and increasing reliance on imported and processed foods threaten the continent’s food sovereignty and public health. This review explores Africa’s contributions to healthy diets and sustainable food systems.ObjectiveTo examine the role of Africa’s traditional diets in promoting global health, and to assess the impact of dietary transitions on nutrition and food security.MethodsA scoping review was conducted using PubMed, Scopus, Web of Science, Google Scholar and some information from FAO repositories. Studies published between 2015 and 2024 were included, with some earlier studies providing historical context. Thematic analysis was used to synthesize findings on African diets, dietary transitions, and global contributions.FindingsTraditional African diets are rich in whole grains, legumes, vegetables, and fermented foods, offering high nutritional value and health benefits. Dietary transitions toward Westernized diets have led to increased consumption of processed foods thus contributing to rising rates of obesity and non-communicable diseases. Africa’s indigenous foods, such as sorghum, millet, teff, amaranth, and baobab, are gaining global recognition for their health benefits. Sustainable food systems in Africa present solutions for addressing global food security challenges.ConclusionAfrica’s traditional food systems provide valuable insights into healthy and sustainable diets. Promoting indigenous African foods and preserving traditional dietary practices can enhance global food security and nutrition. Policies and investments should focus on revitalizing traditional African diets to address nutrition and food security challenges.